CDKL3 shapes immunosuppressive tumor microenvironment and initiates autophagy in esophageal cancer - Bi, Yanping; Liu, Jie; Qin, Songbing; Ji, Fuqing; Zhou, Chao; Yang, Haihua; Zhou, Suna (Frontiers in Immunology, 2024)
Background CDKL3 has been associated with the prognosis of several tumors. However, the potential role of CDKL3 in immunotherapy and the tumor microenvironment (TME) in esophageal carcinoma (ESCA) remains unclear. Methods In this study, Cox regression analysis was used to assess the predictive value of CDKL3 for ESCA outcomes. We systematically correlated CDKL3 with immunological features in the TME. The role of CDKL3 in predicting the efficacy of immunotherapy was also analyzed. Correlation analysis, Cox analysis and LASSO Cox regression were used to construct the CDKL3-related autophagy (CrA) risk score model. The relationship between CDKL3 expression and postoperative pathological complete response (pCR) rate in esophageal squamous cell carcinoma (ESCC) patients undergoing neoadjuvant chemoradiotherapy (nCRT) was evaluated using Immunohistochemical staining (IHC). The relationship between CDKL3 expression and autophagy induction was confirmed by immunofluorescence staining and western blot, and the effect of CDKL3 expression on macrophage polarization was verified by flow cytometry. Results High expression of CDKL3 was found in ESCA and was associated with poor prognosis in ESCA. Moreover, CDKL3 expression was negatively correlated with tumor-infiltrating immune cells (TIICs), the integrality of the cancer immunity cycles, and anti-tumor signatures, while CDKL3 expression was positively correlated with suppressive TME-related chemokines and receptors, immune hyperprogressive genes, and suppressive immune checkpoint, resulting in immunosuppressive TME formation in ESCA. An analysis of immunotherapy cohorts of the ESCA and pan-cancer showed a better response to immunotherapy in tumor patients with lower CDKL3 levels. The CrA risk score model was constructed and validated to accurately predict the prognosis of ESCA. Notably, the CrA risk score of ESCA patients was significantly positively correlated with M2 macrophages. Furthermore, knockdown CDKL3 in KYSE150 cells could inhibit autophagy induction and M2 macrophage polarization. And, radiation could downregulate CDKL3 expression and autophagy induction, while ESCC patients with high CDKL3 expression had a significantly lower response rate after nCRT than those with low CDKL3 expression. Conclusion CDKL3 may play an important role in anti-tumor immunity by regulating autophagy to promote the formation of immunosuppressive TME, thus playing a critical role in the prognosis of ESCA.